Palladium mediated cycloisomerization of sugar alkynols: synthesis of cyclic enol-ethers and spiroketals - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
Functionalized bicyclic enol-ethers and spiroketals are prepared by Pd catalyzed cycloisomerization of 3-C-alkynylfuranosyl derivatives. Cycloisomerization of differently substituted alkyne derivatives revealed a preference for 6-endo-dig cyclization over 5-exo-dig if the substituent is not sufficiently electron withdrawing. The scope of these cycloisomerizations has been further extended by integrating with conjugate addition. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: c-alkynylfuranose; cycloisomerization; enol-ether; Palladium; Spiroketal

Influence of electronic factors on palladium-mediated cycloisomerization: a systematic investigation of competitive 5-exo-dig versus 6-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G. (Tetrahedron, 2008)
Pd-mediated cycloisomerization of 3-C-alkynyl-allo- and ribofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity in ring closure reaction. The reactions in general are influenced by the electronic nature of the substituent on the alkyne unit. A preference for endo-dig cyclization over exo-dig is noted, if the alkynyl substituent is not sufficiently electron withdrawing, (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: C-alkynyl furanose; cycloisomerization; enol ether; Palladium; Spiroketal